Constraining the 19Ne(p,γ)20Na Reaction Rate Using a Direct Measurement at DRAGON - Wilkinson R.; Lotay G.; Lennarz A.; Ruiz C.; Christian G.; Akers C.; Catford W. N.; Chen A. A.; Connolly D.; Davids B.; Hutcheon D. A.; Jedrejcic D.; et al. (EPJ Web of Conferences, 2017)
A direct measurement of the 19Ne(p, γ)20 Na reaction has been performed in inverse kinematics at the DRAGON recoil separator, at an energy ∼ 10 keV higher than previous measurements. The key resonance in the 19 Ne + p system relevant for ONe novae and Type-I X-ray burst temperatures have been successfully measured for the first time. Preliminary estimates of the resonance energy and strength are reported as Ec.m. ≈ 458 keV and ωγ ≈ 18 meV. These results are consistent with previous direct measurements, but disagree with the most recent study of the 19Ne(p, γ)20 Na reaction rate. These preliminary results will be finalised after a forthcoming negative log-likelihood analysis.